Intersectoral care management for older people with cognitive impairment during and after hospital stays [intersec-CM] : study protocol for a process evaluation within a randomised controlled trial - Terese Dehl; Ulf Sauerbrey; Adina Dreier-Wolfgramm; Angela Nikelski; Nino Chikhradze; Armin Keller; Jessica Laufer; Fanny Schumacher-Schönert; Stefan H. Kreisel; Jochen René Thyrian; Wolfgang Hoffmann; Horst Christian Vollmar (Trials, 2021)
Background: In the healthcare system in Germany, different institutions and actors play specific roles in the discharge and transition of patients from hospitals into primary care (Sachverständigenrat zur Begutachtung der Entwicklung im Gesundheitswesen, Wettbewerb an der Schnittstelle zwischen ambulanter und stationärer Gesundheitsversorgung, 2012). However, there are shortcomings in these intersectoral transitions. Especially in older people with cognitive impairment (PCI), discharge management often lacks coordination and cooperation between healthcare providers. This frequently results in higher rates of unscheduled readmission. The project intersec-CM is a randomised controlled trial (RCT) that aims to explore up to what extent an intersectoral care management (ICM) can improve this transition. This ICM is delivered by nurses with special training in care management. The objective of this paper is to describe a mixed-methods process evaluation of the intersectoral care management intervention and the factors that facilitate and inhibit its implementation. Methods: Different study designs for process evaluations from previous literature were collected and analysed according to the dimension implementation fidelity, satisfaction with the intervention, feasible transfer into routine care, optimum point of time, frequency and execution of the intervention, and context factors. Results: The actor-network theory was chosen as the theoretic framework for the process evaluation. Based on this theory, a mixed-methods design was developed to combine and integrate qualitative and quantitative evaluation methods. The qualitative part includes semi-structured interviews using topic guides (phase 1) and later in-depth interviews with narrative portions (phase 3), which will be analysed by using the qualitative content analysis according to Kuckartz. The quantitative survey (phase 2) is conducted with standardised questionnaires. Discussion: Challenges in data collection include the development of interview guidelines, which require different terminologies depending on every specific actor targeted in the intervention. Conducting the interviews, there is a risk of misunderstanding the older PCI by the interviewer and vice versa. However, the combination of qualitative and quantitative approaches as different techniques of process evaluation may help to capture, integrate and analyse data on different dimensions of the intervention. Conclusions: The results of our process evaluation may serve as an implementation guideline for intersectoral care management in the German healthcare system. Furthermore, the approach to evaluate the process of a complex intervention in health care for older PCI may serve as a stimulus to broaden the evidence base also of other complex intervention studies to improve health care for this vulnerable group. The study was ethically approved by the Ethics Committee of the Ernst-Moritz-Arndt University of Greifswald. The study has been registered at the U.S. National Library of Medicine. Trial registration: ClinicalTrials.gov NCT03359408. Registered on 2 December 2017. The approximate date when recruitment to the process evaluation of the study will be completed is 31 May 2021.
Keywords: Case management; Cognitive impairment; Complex intervention; Dementia; Hospital discharge; Implementation fidelity; Intersectoral care management; Process evaluation; Transition